The 3Rs Principle in Animal Experimentation: A Legal Review of the State of the Art in Europe and the Case in Italy - Maestri, Enrico (Biotech (Basel), 2021)
The aim of this paper is to describe the essential points of Italian and European legislation governing the use of animals in biomedical experimentation. A close look will be taken at the principles of the 3Rs, which represent the mainstay of the legal architecture based on which a correct interpretation may be drawn of the legislative documents on animal experimentation. Furthermore, this paper will address the ways in which Directive 2010/63/EU is implemented in Italian legislation on the welfare of laboratory animals. In addition to an assessment of legal issues (such as the scope of jurisdiction of supervisory authorities tasked with issuing authorizations), it will include a discussion of cases of inadequate and insufficient implementation of the requirements laid down by Directive 2010/63/EU. Both the consistency of the interpretation of national legislation with the Directive and the direct effectiveness of the Directive in national law, in which animal testing has been and still is the subject of heated debate between supporters and opponents, will be examined.